2015
DOI: 10.1128/jvi.01285-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants for the Selective Anti-HIV-1 Activity of the All-β Alternative Conformer of XCL1

Abstract: HIV-1 replication is regulated in vivo by a complex network of cytokines and chemokines. XCL1/lymphotactin, a unique metamorphic chemokine, was recently identified as a broad-spectrum endogenous HIV-1 inhibitor that blocks viral entry via direct interaction with the gp120 envelope glycoprotein. HIV-1 inhibition by XCL1 requires access to the alternative all-␤ conformation, which interacts with glycosaminoglycans (GAGs) but not with the specific XCL1 receptor, XCR1. To investigate the structural determinants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…The protein supplied by R&D Systems is tested to demonstrate chemotactic activity, so we conclude that the version of XCL1 used in our experiments was in the classic XCL1 conformation and would not be expected to suppress HIV replication. In fact, the R&D Systems XCL1 was tested recently and was shown to have only modest suppressive activity compared to that of other preparations (53). If XCL1 were to be utilized for anti-HIV therapy, it would need to be formulated in the ␤-dimer form, and a variant with a disulfide bond that stabilizes the all-␤ conformation has been engineered (54).…”
Section: Discussionmentioning
confidence: 99%
“…The protein supplied by R&D Systems is tested to demonstrate chemotactic activity, so we conclude that the version of XCL1 used in our experiments was in the classic XCL1 conformation and would not be expected to suppress HIV replication. In fact, the R&D Systems XCL1 was tested recently and was shown to have only modest suppressive activity compared to that of other preparations (53). If XCL1 were to be utilized for anti-HIV therapy, it would need to be formulated in the ␤-dimer form, and a variant with a disulfide bond that stabilizes the all-␤ conformation has been engineered (54).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that the metamorphic behavior of XCL1 plays an important role in its biological activity. For example, the alternative XCL1 dimer conformation inhibits HIV infection in peripheral blood mononuclear cells, but the monomeric chemokine fold does not (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…12 Mutational analysis indicated that the anti-HIV-1 activity of XCL1 depends on residues that also participate in GAG binding. 13 A link between XCL1–GAG binding and antiviral potency may reveal the evolutionary advantage conferred by the metamorphic XCL1 native state.…”
mentioning
confidence: 99%